Hubungan antara Dukungan Keluarga dengan Distress Pasien Diabetes Mellitus Tipe 2 - Ainur Azzahra Aroby; Suyanto Suyanto; Indah Sri Wahyuningsih (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Type 2 Diabetes Mellitus which is increasingly common is often accompanied by complications and psychological problems such as stress. The level of stress in diabetes patients can be influenced by family support which plays a crucial role in improving their quality of life. This study aims to examine the relationship between the level of family support and stress levels in patients with type 2 diabetes mellitus. The method used in this study is a quantitative approach with a cross-sectional research design. A total of 132 type 2 DM patients registered at the Genuk Health Center, Semarang, were randomly selected as samples. Data were analyzed using the Chi-Square test, and the results showed a significant relationship between family support and patient stress levels (p-value = 0.047). This indicates that adequate family support plays an important role in reducing stress in type 2 diabetes patients.